Analisis Spasio-Temporal Kualitas Udara Ambien (NO₂ dan SO₂) Serta Pengaruh Faktor Meteorologi di Kawasan Mega Mas Kota Manado - Mega Melati Putri Kansil; Oksfriani Jufri Sumampouw; Fima L. F. G. Langi (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Commercial areas with dense motorized vehicle activity, such as Mega Mas in Manado City, are sources of ambient air pollutant emissions, especially Nitrogen Dioxide (NO₂) and Sulfur Dioxide (SO₂). Exposure to these pollutants has the potential to cause negative impacts on public health and the environment. This study aims to analyze ambient air quality based on NO₂ and SO₂ parameters and meteorological factors (temperature, humidity, wind speed) at the exit portal of the Mega Mas Area. Research Methods: This study is observational with a cross-sectional approach. Sampling was carried out purposively at two points (Point 1 MTC and Point 2 in front of IT) in the morning and afternoon, with two replications per point. The concentrations of NO₂ and SO₂ were measured using a High Volume Air Sampler (HVAS) with the Griess-Saltzman and Pararosanilin methods, then analyzed spectrophotometrically. The data were analyzed descriptively for univariate (variable characteristics), bivariate (meteorological parameters and pollutant relationships), and spatial-temporal analysis. Research Results: The measurement results showed that NO₂ concentrations ranged from 2-22 µg/Nm³, while SO₂ between 4-14 µg/Nm³. All of these values ​​are still far below the Threshold Limit Value (NAB) according to the Indonesian Minister of Health Regulation No. 2 of 2023. The analysis showed a high variation in concentration, especially NO₂ at Point 1 in the afternoon (22 µg/Nm³). Wind speed was shown to have a significant effect on pollutant dispersion, where the highest concentration was recorded at low wind speeds (2.5-2.7 m/s). Vehicle activity patterns and microlocation conditions that inhibit dispersion are suspected to be the main causes of the observed variations. Conclusion: It was concluded that the ambient air quality at the exit portal of the Mega Mas Area based on NO₂ and SO₂ parameters still meets quality standards. However, significant fluctuations in concentrations, particularly during calm wind conditions, indicate the potential for local accumulation of pollutants. Routine monitoring and proper traffic management are required to minimize pollutant exposure, especially for workers working in the area for long periods.